Organizational justice and organizational identification of millennials in mergers and acquisitions: a conceptual framework - Ismail, Maimunah; Bebenroth, Ralf (Eurojournals, 2016)
This article proposes a conceptual framework of influence of organizational justice on organizational identification of Millennials in mergers and acquisitions (M&As). An extensive literature review method was employed to identify and analyse relevant literatures, and was driven by the Person-Environment Fit theory. This research focuses only on Millennials owing to the significant increase of this generation cohort in many countries’ workforce. The authors identified potential predictors of three dimensions of organizational justice, viz. distributive justice, procedural justice, and interactional justice on organizational identification as perceived by Millennials in M&As. Future research should validate and examine the predictive power of the proposed relationship. The paper could offer practical implications to human resource managers, communication managers,and employees to assist in the M&A process by understanding organizational identification resulting from organizational justice. In an M&A deal one should take cognizance of specific relationships between organizational justice dimensions and organisational identification from the perspective of the Millennials. The paper uses the Person-Environment Fit theory in conceptualizing organizational identification by linking it with organizational justice dimensions in an M&A context and it further adds value to conceptualizing organizational identification.